CORRUPTION IS A LEADING BARRIER FOR THE DEVELOPMENT OF A COUNTRY (ResearchJet Journal of Analysis and Inventions, 2021)
In this article we will discuss the types of corruption thoroughly and the impact of corruption on the wellbeing of the population. Besides, the strategies to counter corruption are claimed in a number of examples.